2022
DOI: 10.12688/f1000research.77430.2
|View full text |Cite
|
Sign up to set email alerts
|

Can enhancement and suppression concurrently guide attention? An assessment at the individual level

Abstract: Background: Although people can pay attention to targets while ignoring distractors, previous research suggests that target enhancement and distractor suppression work separately and independently. Here, we sought to replicate previous findings and re-establish their independence. Methods: We employed an internet-based psychological experiment. We presented participants with a visual search task in which they searched for a specified shape with or without a singleton. We replicated the singleton-presence benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
3
1
Order By: Relevance
“…Our conclusions are seemingly at odds with recent studies investigating both distractor suppression and target enhancement in a similar search and probe task (Chang & Egeth, 2019, 2021Hamblin-Frohman et al, 2022). There, attentional enhancement for target features has consistently been found, along with evidence for suppression of singleton distractor features (but see Kawashima & Amano, 2022). Two methodological variations in the Chang and Egeth design could account for the differences, and suggest caution in comparing their findings with those using the classic capture-probe paradigm.…”
Section: Gtfe Parsimoniously Explains Difference In Attention Among D...contrasting
confidence: 95%
See 2 more Smart Citations
“…Our conclusions are seemingly at odds with recent studies investigating both distractor suppression and target enhancement in a similar search and probe task (Chang & Egeth, 2019, 2021Hamblin-Frohman et al, 2022). There, attentional enhancement for target features has consistently been found, along with evidence for suppression of singleton distractor features (but see Kawashima & Amano, 2022). Two methodological variations in the Chang and Egeth design could account for the differences, and suggest caution in comparing their findings with those using the classic capture-probe paradigm.…”
Section: Gtfe Parsimoniously Explains Difference In Attention Among D...contrasting
confidence: 95%
“…In these studies, separable effects of target enhancement and distractor suppression on probe performance were investigated by explicitly comparing probe item processing against nonsingleton probes appearing in “neutral” colors. The studies all showed large effects of facilitation by target features, and of suppression associated with singleton distractors, except for an online replication which did not find the suppression effect (Kawashima & Amano, 2022). A notable difference between these four studies and the classic capture-probe task is that the former used cued report of a single probe, rather than the free recall task of the original.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Chang and Egeth (2019) used this approach in a variant of the probe paradigm in which participants occasionally switched from looking for a shape in the search trials to looking for the target letter A or B amongst three other letters in the probe trials. They found longer RTs when the target letter A or B was presented on the distractor color object rather than on a neutral color object (but see Kawashima & Amano, 2022). Hamblin-Frohman et al (2022) reported a similar effect when measuring eye fixations.…”
Section: Discussionmentioning
confidence: 98%